THE DIGITAL DATA REVOLUTION: 25 YEARS OF DATA MANAGEMENT EVOLUTION - Vijaya Sekhar Godavarti (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The evolution of data management systems over the past quarter-century represents a fundamental transformation in how organizations handle, process, and utilize digital information. This comprehensive article examines the journey from the era of structured data to the current age of complex, multi-dimensional data management. It covers the emergence of social media platforms and their impact on data generation, the development of sophisticated data management systems, and the rise of modern architectural components. The article explores critical aspects of data governance, security frameworks, and environmental considerations in data center operations. Special attention is given to emerging trends, including edge computing, artificial intelligence in data management, and sustainable practices. The article demonstrates how organizations have adapted to exponential data growth while maintaining efficiency, security, and environmental responsibility, highlighting the continuous evolution of data management strategies to meet contemporary challenges.